2012
DOI: 10.1371/journal.pone.0030922
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Evaluation of Retinal Neurodegeneration in Patients with Multiple Sclerosis

Abstract: ObjectiveTo evaluate macular morphology in the eyes of patients with multiple sclerosis (MS) with or without optic neuritis (ON) in previous history.MethodsOptical coherence tomography (OCT) examination was performed in thirty-nine patients with MS and in thirty-three healthy subjects. The raw macular OCT data were processed using OCTRIMA software. The circumpapillary retinal nerve fiber layer (RNFL) thickness and the weighted mean thickness of the total retina and 6 intraretinal layers were obtained for each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 37 publications
(53 reference statements)
3
41
1
2
Order By: Relevance
“…24 Although manual grading of intraretinal layers is time consuming, it may provide some advantage for repeatability testing. Commercial and custom software, such as the one used by Cabrera DeBuc et al, [15][16][17] often requires manual correction of segmentation failure, which may not be necessarily related to the accuracy of the measurement. 16,17,54 Segmentation algorithms used in OCT reading centers often require visual inspection after automatic segmentation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Although manual grading of intraretinal layers is time consuming, it may provide some advantage for repeatability testing. Commercial and custom software, such as the one used by Cabrera DeBuc et al, [15][16][17] often requires manual correction of segmentation failure, which may not be necessarily related to the accuracy of the measurement. 16,17,54 Segmentation algorithms used in OCT reading centers often require visual inspection after automatic segmentation.…”
Section: Discussionmentioning
confidence: 99%
“…The custom-built software, which has been described elsewhere, [15][16][17][18] was used to manually and automatically segment these layers. Because the manual segmentation is labor intensive and time consuming, a particular approach was used to outline the boundaries of these layers in a small area nasally from the fovea.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…55 Some studies have shown an inverse relationship between inner nuclear layer thickness and EDSS (progression). 56,57 Recently, a strong correlation between ganglion cell/inner plexiform atrophy and whole-brain, especially GM, atrophy, was established, particularly in patients with progressive MS, suggesting that it mirrors underlying disease progression. 58 Despite promising results, more large longitudinal studies are needed to evaluate the prognostic value of optical coherence tomography (OCT) in MS. A limitation of OCT is that measurements are affected by a history of ON, lesions elsewhere in the visual pathway and non-MS ocular conditions.…”
Section: Predicting Disease Progressionmentioning
confidence: 99%
“…By employing the OCT technique, the thickness and volume measurements of the retinal tissue can be obtained from OCT scans. Particularly, the structural alterations revealed by changes in thickness and volume of the cellular layers of the retina can be measured to characterize the neurodegeneration in patients with diabetes [2][3][4][5][6][7]. The most significant retinal pathology caused by diabetes is diabetic retinopathy (DR), which is characterized by blood vessel damage and neurodegenerative changes.…”
Section: Introductionmentioning
confidence: 99%